Gerenciamento de resíduos de construção e demolição aliado a ações de produção mais limpa - Garbin, Júlio César (2022)
With the strong increase in civil construction in our country, much has been discussed in the search for ways to minimize the damage that can be caused to the environment, and one way to reduce this is to control the generation of waste, known as Waste of Civil Construction (WCC). In this sense, in 2002, the National Council for the Environment published Resolution No. 307, which provides definitions of WCC. This resolution establishes procedures for the management of civil construction waste, establishing obligations for both the generator and the municipalities to dispose of these materials in an environmentally correct way. The reuse of these residues, in addition to the environment benefit, can be a new form of economic valuation of these materials. The idea that this study followed, used the stages of management of RCC in the different classes defined by CONAMA Resolution number 307/2002. With this, a characterization of the waste was carried out, its separation and packaging, in two different small works, being a construction of a house and a renovation of a house. Obtaining positive results in terms of control of input material and output of waste, managing to reuse part of the waste, and the rest not being reused correctly, in addition to seeking sources of savings for future works. With the results found, it was observed that a house renovation generates 71% more rubble, being this class A waste, when compared to a new construction, which also has rubble as the biggest waste generation. As the main action combined with cleaner production, we have the control and separation of input and output of materials, which contributes to the reuse of materials in the same job and in others jobs. Thus, a management plan for solid waste in works is necessary to reduce the environmental impacts resulting from this activity, and combined with cleaner production, it allows civil works to become more sustainable.